The Role of Women in Improving Family Economy Amid COVID-19 Pandemic - Lubis, Rini Hayati; Napitupulu, Rodame Monitorir; Izzah, Nurul (AL-QARDH, 2022)
Since June 2020, Padangsidimpuan city was designated as a yellow zone during the Covid-19 pandemic. It has an impact on the household economy. These conditions pushed women to contribute in improving the family economy. The aim of this research is to know the role of women in the family economy improvement in the middle of the Covid-19 pandemic. The research used qualitative descriptive method with a total sample of 108 women. The result showed that 73 percent of sample have decreased income and 47 percent family spending increased during the Covid-19 pandemic. These impulse women to work for initiatively helping the family economy as the main goal. A total of 80 percent of self-employed entrepreneurs were trading, with a productive age of 28-54 years dominated by high school education as the background. The amount of revenue reached Rp 50,000-150.00 per day with an average total of dependent inside a family is 4 people. This means that women in the household could still improve the family economy. Therefore, it is necessary using technology to promote business through e-marketing such as: social media, promotion banners (delivery order) via mobile phone or Whatsapp. In addition, e-Marketing education in women is important to be noticed by various parties.